All optical CSRZ generator - Mohd Ekhmal Azizan (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
The Carrier-Suppressed Return-to-Zero (CSRZ) conversion signal is an optical modulation format used in high bit rate transmission system and long-haul data transmission. The characteristics of CSRZ provide a better candidate for transmission system. The 10Gbit/s all optical format conversion from non return-to-zero (NRZ) to carrier-suppressed return-to-zero (CSRZ) and conversion between return-to-zero (RZ) and CSRZ are simulated in this project by using a SOA-based fibre loop mirror design circuit. All the conversions are done by using Optisytem software design tool. The converter operates with control light composes of 5-Ghz sinusoidal optical clock signal and a continuous / wave light. The WDM system is also simulated in this project. The ability of the design system in converting the signal to CSRZ is studied. This project also presents the conversion of CSRZ back to RZ and NRZ by using the same converter. In RZ to CSRZ and NRZ to CSRZ conversions, the closest data frequency with control light frequency is also simulated by using the same converter design system.